Surface and textural analyses for bimetallic nickel-based catalyst onto various support using microwave assisted synthesis - Samidin, Salma; Lahuri, Azizul Hakim; Wan Isahak, Wan Nor Roslam; Ahmad, Khairul Naim; Yusop, Muhammad Rahimi; Dzakaria, Norliza (Malaysian Institute of Chemistry, 2024)
The synthesis of a bimetallic nickel catalyst via the integration of different support materials comprising Al2O3, SiO2, and dolomite was analysed and compared. The catalysts were synthesised using a microwave monomode reactor for 11 minutes at a temperature of 160 °C. The primary characterisation methods utilised for the investigation of reduction behaviour were temperature-programmed reduction (TPR), X-ray diffraction, and N2 adsorption-desorption isotherm. The original structure of oxides Ni and Cr-Ni can be altered using silicon dioxide (SiO2), aluminium oxide (Al2O3), and dolomite (CaMg(CO3)2), which have all been subjected to research, indicating that there is a significant interaction between the catalyst and support. After the addition of the support, the distribution determined using Barrett-Joyner-Halenda (BJH) calculations indicates a broad pore size range that encompasses both meso (2-50 nm) and macro pore (>50 nm). In comparison to catalysts alone, oxides of Ni and Cr-Ni that contain SiO2 have a greater surface area. Whereas SiO2 was found to effectively enhance the surface area of oxide Ni compared to Al2O3 and dolomite as supporting materials. The utilisation of SiO2 on the Ni-based catalysts caused the temperature of the TPR peak to decrease to 392 °C, compared to Al2O3 and dolomite. This may be attributed to two factors: weak interaction on SiO2, the surface area, and porosity thus leading to easier diffusion of gas reductant, and accessibility of reactants during reduction thus enhancing the reduction of NiO species.